Adaptive lifestyle of bacteria determines phage-bacteria interaction - Ulrich, Laura; Giez, Christoph; Steiner, Leon X.; Hentschel, Ute; Lachnit, Tim (Frontiers in Microbiology, 2022)
Bacteriophages and their interactions with microbes are not well understood. As a first step toward achieving a better understanding, we isolated and sequenced the Curvibacter phage PCA1 for the purpose of eliminating Curvibacter sp. AEP1.3, the main colonizer of Hydra vulgaris AEP. Our experiments showed that PCA1 phage caused a strong, virulent infection only in sessile Curvibacter sp. AEP1.3 but was unable to infect planktonic and host-associated bacterial cells of the same strain. In an effort to investigate this phenomenon, we compared sessile, planktonic and host-associated bacteria via RNA sequencing and found that all three states differed significantly in their expression patterns. This finding led us to propose that the adaptive lifestyle of Curvibacter sp. AEP1.3 results in varying degrees of susceptibility to bacteriophage infection. This concept could be relevant for phage research and phage therapy in particular. Finally, we were able to induce phage infection in planktonic cells and pinpoint the infection process to a membrane protein. We further identified potential phage-binding protein candidates based on expression pattern analysis.